The Self-Focus Methodology: Entrepreneurial Competencies in Creactivate 4.0 Participants - Lozano, Carmen (2023)
This article examines the impact of the self-focus model (MES) on the entrepreneurial competencies of a group of participants in the Creactivate 4.0 entrepreneurship program in 2020, and reexamines the evaluation of competencies using the entrepreneurial mindset profile test (EMP) in the pre-test versus post-test modality, and makes a comparative analysis of the competencies in the sample of entrepreneurs evaluated and involved. Several aspects of the emotional and psycho-affective challenges that the averageentrepreneur has to face were collected. To accompany the sample of Creactivate 4.0 entrepreneurs, the evaluation of competencies with EMP and individual and group accompaniment focused on strengthening competencies and applying the EMP post-test to observe the development of entrepreneurial competencies. The results showed that through the post-test, a significant increase in entrepreneurial skills and a mobilization of personality traits directly associated with the entrepreneurial mindset, increased thedegree of empowerment with their business units and the implementation of strategies to increase income.